2019
DOI: 10.1021/acs.jpca.8b12003
|View full text |Cite
|
Sign up to set email alerts
|

Nature and Strength of M–H···S and M–H···Se (M = Mn, Fe, & Co) Hydrogen Bond

Abstract: The significance of dispersion contribution in the formation of strong hydrogen bonds (H-bonds) can no more be ignored. It was illustrated that less electronegative and electropositive H-bond acceptors such as S, Se, and Te are also capable of forming strong N–H···Y H-bonds, mostly due to the high polarizabilities of H-bond acceptor atoms. Herein, for the first time, we report the evidence of formation of nonconventional M-H···Y H-bonds between metal hydrides (M-H, M = Mn, Fe, Co) and chalcogen H-bond acceptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 62 publications
(124 reference statements)
0
23
0
1
Order By: Relevance
“…Interestingly, in 2016, Zhang and coworkers reported that the same substrate ( 1 o ) in the Co(OAc) 2 /Ag 2 CO 3 system gave carbonylation product 5 . In the same year, Baidya and coworkers independently reported that 1 o with DEAD in the Cu(OTf) 2 /Ag 2 CO 3 system gave amidation product 3 o (Scheme ). Our studies demonstrated that our Ag‐catalyzed approach is highly regioselective for the C5‐position of the quinoline and produces C−H amidation product 3 o without Pd, Cu, or Co catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in 2016, Zhang and coworkers reported that the same substrate ( 1 o ) in the Co(OAc) 2 /Ag 2 CO 3 system gave carbonylation product 5 . In the same year, Baidya and coworkers independently reported that 1 o with DEAD in the Cu(OTf) 2 /Ag 2 CO 3 system gave amidation product 3 o (Scheme ). Our studies demonstrated that our Ag‐catalyzed approach is highly regioselective for the C5‐position of the quinoline and produces C−H amidation product 3 o without Pd, Cu, or Co catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…For example, hydrazide product 3aa could be straightforwardly transformed into p-phenylenediamine (8) in 70 % yield by removal of the Cbz group and cleavage of the N-N bond in a single step. [7] One of the advantages to have a free amine in reactions is the possibility to remove or use it in other transformations. [15] By means of the well-known Sandmeyer reaction, diazotization of 3aa with NaNO 2 followed by treatment with NaI produced 4-iodophenylhydrazine (9) in 73 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…[6] Moreover, a similar process was reported with readily available azodicarboxylates (Scheme 1c). [7] However, the introduction and subsequent removal of protecting groups not only requires addi-found to be highly regioselective and provided a series of paminophenylhydrazine derivatives in excellent yields. Moreover, compatibility with a free amino group makes this protocol an attractive strategy in synthetic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the development of chelation‐assisted transition‐metal catalysis has provided a new complementary route for facile construction of various C−N bonds . Reactions of copper‐chelation system can be performed even at room temperature ,,. The intramolecular dehydrogenative amidation protocol have been well established by researchers such as Shi, Kanai, Ge,, Shi, and Bedford (Scheme c).…”
Section: Methodsmentioning
confidence: 99%